Src Inhibitors as Potential Therapeutic Agents for Human Cancers - Trevino, Jose G.; Summy, Justin M.; Gallick, Gary E. (Mini Reviews in Medicinal Chemistry, 2006)
Selective inhibitors of the Src family of protein tyrosine kinases have been developed as therapeutic agents for human tumors, some of which are now in various stages of clinical trial. In this review, recently described novel small molecule ATP-competitive Src inhibitors are discussed, with an emphasis on their potential use as therapeutic inhibitors for advanced-stage malignancies.
Keywords: Src family kinase